The Use of Cell Phones in Accessing Social Media by Students During Learning Process in English Classroom - Fadillah, Ridha; Purnawarman, Akhmad Adi (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
This study investigates a phenomenon in the educational world: using cell phones during teaching and learning in English classes. Cell phones here are referred to as inappropriate use, not as a supportive device in teaching and learning, reducing students' attention span. This research was conducted in 2 high schools, one in Lombok City, West Nusa Tenggara, and one in Banjarbaru City, South Kalimantan. Fifteen students were involved in this research as respondents, and 2 English teachers as informants. Random sampling was used to determine the research sample. Interview techniques were used to collect data. The research results indicated that all respondents used cell phones to access their social media accounts during the teaching and learning process in the class, ranging from 5 minutes to 30 minutes in 1 lesson to reduce boredom in class. A negative impact of using cell phones is that this action can divide and reduce students' attention to the lessons, which can ultimately reduce students' understanding of English subjects. The study recommends that teachers be aware of this phenomenon and always activate the students by presenting appropriate teaching methods and materials.